PEMANFAATAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN DI KELAS V SDI DARUL MUTTAQIEN - Zahra Tri Amarwati; Siska Kusumawardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of the Canva application by fifth-grade teachers is a visual learning innovation that makes it easier for students to understand the material. This effort aims to create an active, critical, collaborative, and creative learning process. However, there are still students who are less active during learning, becoming a challenge in optimizing digital media. This study aims to describe the use of the Canva application as a learning medium in fifth-grade SDI Darul Muttaqien. The study used a descriptive qualitative method with fifth-grade teachers and students as subjects. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results show that the Canva application makes a positive contribution to learning, supporting creativity, learning motivation, and student collaboration. The Canva application also supports the implementation of the Merdeka Belajar (P5) program with the theme